The impact of the first 2 years of the COVID-19 pandemic on breast cancer diagnoses: a population-based study in England - Gathani, T; Dodwell, D; Horgan, K (Springer Nature, 2022)
Cancer services were seriously disrupted during the COVID-19 pandemic. Using publicly available data for England, we show that breast cancer diagnoses decreased substantially in the first year of the pandemic, but have recovered to at least pre-pandemic levels. Long term follow-up is needed to assess the impact on outcomes.